MINERAL SEQUESTRATION OF CARBON DIOXIDE IN A SANDSTONE-SHALE SYSTEM - Xu T.; Apps J.A.; Pruess K. (My University, 2005)
A conceptual model of CO2 injection in bedded sandstone-shale sequences has been developed using hydrogeologic properties and mineral compositions commonly encountered in Gulf Coast sediments. Numerical simulations were performed with the reactive fluid flow and geochemical transport code TOUGHREACT to analyze mass transfer between sandstone and shale layers and CO2 immobilization through carbonate precipitation. Results indicate that most CO2 sequestration occurs in the sandstone. The major CO2 trapping minerals are dawsonite and ankerite. The CO2 mineral-trapping capacity after 100,000 years reaches about 90 kg/m3 of the medium. The CO2 trapping capacity depends on primary mineral composition. Precipitation of siderite and ankerite requires Fe+2 supplied mainly by chlorite and some by hematite dissolution and reduction. Precipitation of dawsonite requires Na+ provided by oligoclase dissolution. The initial abundance of chlorite and oligoclase therefore affects the CO2 mineral-trapping capacity. The sequestration time required depends on the kinetic rate of mineral dissolution and precipitation. Dawsonite reaction kinetics is not well understood, and sensitivity regarding the precipitation rate was examined. The addition of CO2 as secondary carbonates results in decreased porosity. The leaching of chemical constituents from the interior of the shale causes slightly increased porosity. The limited information currently available for the mineralogy of natural high-pressure CO2 gas reservoirs is also generally consistent with our simulation. The "numerical experiments" give a detailed understanding of the dynamic evolution of a sandstone-shale geochemical system. © 2005 Elsevier B.V. All rights reserved.
Keywords: BEDDED SANDSTONE-SHALE; CO2 SEQUESTRATION; MINERAL TRAPPING; NUMERICAL SIMULATION